The Impact of Using Mobile Phones at SMP Negeri 11 Sarolangun Jambi - Juliansi, Niken Armanda; Fauzi, Taty; Surtiyoni, Endang (CV. Rayyan Dwi Bharata, 2024)
The Impact of Mobile Phone Use in SMP Negeri 11 Sorolangun Jambi. Has a formulation and purpose, is: How the impact of Mobile Phone use on the learning behavior of grade VIII students at SMP Negeri 11 Sorolangun Jambi, and aims to describe the results of research on social behavior and student learning. The research method used is a qualitative descriptive analysis based on the philosophy of positivism with data collection techniques: observation, interviews, questionnaire surveys, and documentation and data analysis using Miles and Huberman techniques, consisting of: data reduction, data display, and conclusion drawing/verification